MENCARI CELAH PENANAMAN NILAI-NILAI PANCASILA PADA GENERASI MILENIAL - Nichi Hana Karlina (Universitas Informatika dan Bisnis Indonesia, 2018)
For millenial generation, the use of gadgets has become a lifestyle even social media has now become a communication space. Millennial or Z generations are those born after the 1980s, have specific tendencies on political views, communication and worldviews on world issues. Similarly, their perspective on the values ??of Pancasila, which allegedly began to fade. The purpose of this research is to know the description of millenial generation of Indonesia in order to design the right strategy in effort to ground Pancasila. So that Pancasila is not only considered as the state ideology, but also as a view of life, especially among millennial youth. The research method in this research is qualitative research, the research data is obtained from the results of literature study and Focus Discussion Group (FDG) held by UKP-PIP (Presidential Work Unit of Ideology Development of Pancasila) on December 29, 2017 at Luxton Hotel Bandung, to know the opinion from various circles, communities and professions associated with millennial generation. By knowing the full picture of the millennial generation, it is hoped that they will be able to design the right strategy in the effort to ground Pancasila, so as to create the virtuous generation of Indonesia based on Pancasila. Keywords: Pancasila, Generation, Millenial